Peningkatan Kemampuan Anak Kelompok B dalam Berhitung Melalui Permainan Karpet Angka di TK Islam Al Ishlah Kota Bukittinggi - Elvi Wahyuni; Chindra Chindra; Erniati Erniati (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study aims to improve children's counting skills in group B in counting. Through the number carpet game at Al Ishlah Islamic Kindergarten, Mandiangin Koto Selayan District, Bukittinggi City. Departing from the low ability of children to count, in this case the researcher is interested in trying to improve learning activities to increase children's interest and motivation so that children's understanding of learning becomes better. The learning improvement process is carried out using the game method which is carried out in two cycles. Researchers collect initial data, data on the development of the learning improvement process and children's learning outcomes which are then reflected on to draw conclusions to determine and plan actions in the next cycle. Then conclude the results of the implementation of the learning improvement process after the cycle ends. The findings of researchers after carrying out corrective actions show that there has been a significant increase, this can be seen from the increase in the average score obtained by children from Starting to Develop (MB) in cycle I, to Developing As Expected (BSH) and Developing Very Well (BSB) in cycle II. With this increase, it can be said that the implications of classroom action research by applying number carpet games have improved children's counting skills in group B. Islamic Kindergarten Al Ishlah Bukittinggi City. Keywords: Counting Ability, Number Carpet Media, Game Method